Choroidal Thickness in Patients Diagnosed with Human Immunodeficiency Virus Infection: Results from Two Populations of Different Ethnicities. (19th May 2019) - Agarwal, Aniruddha; Invernizzi, Alessandro; Jain, Sahil; Acquistapace, Alessandra; Riva, Agostino; Sharma, Aman; Gupta, Vishali; Singh, Ramandeep
ABSTRACT: Purpose : To measure the choroidal thickness among subjects with human immunodeficiency virus (HIV) infection from two diverse ethnic populations and to compare it with healthy controls. Methods : Subjects with HIV infection and healthy controls were enrolled in two referring centers in Italy and India. Clinical data were collected. All subjects underwent enhanced-depth imaging optical coherence tomography and measurement of choroidal thickness. Results : A total of 68 eyes from 68 patients with HIV (44 Caucasian, 24 Indians) and 60 eyes from 60 healthy volunteers (36 Caucasian, 24 Indians) were included. Mean choroidal thickness was significantly higher in HIV patients compared to controls (312.91 ± 65 µm vs. 266.57 ± 47 µm; p  < 0.001). Choroidal thickness was higher among subjects with HIV-related retinopathy compared to HIV without retinopathy (285 ± 30 µm vs. 352 ± 17 µm; p  < 0.01). Conclusions : Patients with HIV infection, especially with HIV microangiopathy, have thicker choroid compared to age- and gender-matched healthy control subjects. These changes may be related to HIV-associated choroidal vascular dysfunction.